The role of evaporite in iron oxide-apatite ore deposit formation: constraints of the late Miocene Abovyan deposit, Armenia - Nekrylov, Nikolai; Hovakimyan, Samvel; Meliksetian, Khachatur B.; Veress, Ervin; Bergemann, Christian A.; Hambaryan, Karen; Chiaradia, Massimo; Vardanyan, Arman; Navasardyan, Gevorg; Korneeva, Alina; Kamenetsky, Vadim S.; Moritz, Robert (Lithos, 2025)
Iron Oxide-Apatite (IOA) deposits are a notable source of iron, and, potentially, of phosphorus and rare earth elements (REE). The vast majority of these deposits are ancient (from ∼1900 to ∼100 Ma), and their original textures and mineral associations are overprinted by regional and local metasomatic/metamorphic processes. In the present paper, we provide new petrographic, mineralogical and geochemical data on the poorly studied Abovyan IOA deposit in Armenia, one of the world's youngest IOA deposits. The Late Miocene magnetite-apatite Abovyan deposit is hosted by a subvolcanic andesite body located in the volcanic zone of Gegham Highland. The ore mineralization is hosted in andesite and consists of disseminated magnetite‑carbonate blobs, breccia and massive magnetite-apatite bodies. Disseminated blobs mostly consist of magnetite-clinopyroxene-dolomite-hematite-calcite assemblages, whereas the mineralogical diversity increases toward the massive ore bodies with the appearance of Th- (thorite, monazite) and REE-rich (monazite, REE-silicates) minerals. Abundant inclusions of halite and sylvite were also found in magnetite from massive ore. Massive magnetite-apatite ore is depleted in Rb, Ba, K, Sr and HFSE and enriched in REE, Th, U and Pb relative to host andesite. The host rocks have more radiogenic 87Sr/86Sr ratios of ∼0.7053 than other volcanic rocks in the Gegham highland with ratios of ∼0.7042. The apatite from nine ores samples have even more radiogenic 87Sr/86Sr ratios of ∼0.706 for the same εNd values. These data allow us to conclude that ore formation is likely linked to liquid immiscibility triggered by the assimilation of Sr-rich and Nd-poor crustal material. The local source for such assimilated material is the K-rich evaporite of the Yerevan salt basin.